2021
DOI: 10.3390/plants10050834
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Profile and Screening of Bioactive Metabolites of Rindera graeca (A. DC.) Bois. & Heldr. (Boraginaceae) In Vitro Cultures

Abstract: Rindera graeca is a rare endemic plant where in vitro culture has been used in order to investigate bioactive metabolites. Phytochemical study of the in vitro shoots and hairy roots led to the isolation of seven phenolic derivatives and the unusual furano-naphthoquinone rinderol. R. graeca was also analyzed for its pyrrolizidine alkaloids content by LC-MS, and it was found to contain echinatine together with echinatine and rinderine N-oxides. Rinderol, isolated only from in vitro hairy root culture for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 28 publications
1
15
2
Order By: Relevance
“…This species is recognized as rare species and placed on the ICUN Red List of Threatened Plants [6]. The chemical profile of aerial parts [7], as well as shoots and roots cultivated in vitro [8][9][10][11] of this species, has been investigated. These studies revealed the presence of phenolic compounds, pyrrolizidine alkaloids, naphthoquinone shikonin-type compounds and among them rinderol, a potent cytotoxic agent [7,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This species is recognized as rare species and placed on the ICUN Red List of Threatened Plants [6]. The chemical profile of aerial parts [7], as well as shoots and roots cultivated in vitro [8][9][10][11] of this species, has been investigated. These studies revealed the presence of phenolic compounds, pyrrolizidine alkaloids, naphthoquinone shikonin-type compounds and among them rinderol, a potent cytotoxic agent [7,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical profile of aerial parts [7], as well as shoots and roots cultivated in vitro [8][9][10][11] of this species, has been investigated. These studies revealed the presence of phenolic compounds, pyrrolizidine alkaloids, naphthoquinone shikonin-type compounds and among them rinderol, a potent cytotoxic agent [7,11,12]. Rinderol production was optimized in root cultures of R. graeca and its proapoptotic activity was demonstrated [13].…”
Section: Introductionmentioning
confidence: 99%
“…Supplementary materials contain comprehensive overview of representative chromatograms from each root line (Figures S1-S3). occurring naturally in mountain territories of Greece [12]. Biotechnological method developed under conditions of the current study, allows producing rinderol via bioengineering technique applying PUF rafts for root immobilization.…”
Section: Hplc Dad Analysis Of R Graeca In Vitro Root Culturesmentioning
confidence: 98%
“…& Heldr. (Boraginaceae) cultivated in vitro and its structure was elucidated using spectral methods ( 1 H/ 13 C, 1 H-1 H and 1 H- 13 C correlation NMR spectroscopy, ESI-MS) [12]. The structure was also identified as naphthofuranin A in collected in Kunming (China) Onosma paniculata (Bur.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation